FGF21: The Center of a Transcriptional Nexus in Metabolic Regulation - C. Adams, A.; Kharitonenkov, A. (Current Diabetes Reviews, 2012)
Fibroblast growth factor 21 (FGF21) is emerging as a key regulator of energy homeostasis and presents a novel target for the development of therapies for the treatment of diabetes, cardiovascular disease and obesity. Recent publications have demonstrated that FGF21 resides downstream of a complex network of transcriptional regulators which modulate its expression in response to a wide array of physiological stimuli or pharmacologic agents. The manner in which these mechanisms are integrated to regulate FGF21 transcription, production and subsequent secretion is poorly understood. While FGF21 is detected in many metabolically active tissues and is regulated by several of the known transcription factors involved in metabolic control little is known about how these pathways are integrated. In this review, we discuss the data presented to date on regulation of FGF21 by a wide array of transcription factors and explore how it relates to metabolic regulation in vivo.
Keywords: pharmacologic agents